Multiple Periodic Solutions of a Nonautonomous Plant-Hare Model. (25th December 2013) - Gao, Yongfei; Wong, P. J. Y.; Xia, Y. H.; Yuan, Xiaoqing
Abstract : Based on Mawhin's coincidence degree theory, sufficient conditions are obtained for the existence of at least two positive periodic solutions for a plant-hare model with toxin-determined functional response (nonmonotone). Some new technique is used in this paper, because standard arguments in the literature are not applicable.